إثر انموذج كارول باستخدام وسائل تعليمية مساعدة في تعلم بعض المهارات الاساسية بكرة قدم الصالات للطلاب (Journal of the College of Basic Education, 2025)
The aim of the research was to determine the effect of the Carroll Learning Model on teaching basic futsal skills, the effect of the Carroll Learning Model using aided teaching methods to teach basic futsal skills, and to identify which methods are best for teaching basic futsal skills between the experimental and control groups. The research population was intentionally selected, representing (117) second-grade intermediate students from Othman Al-Obaidi Intermediate School for Boys, a school in the Baghdad Education Directorate of Rusafa/3, for the academic year 2024-2025. The research sample was selected by lottery. Thus, the sample consisted of (60) students: (20 students representing Class A, with whom Carroll's model was used; (20) students representing Class B, with whom Carroll's model was used in conjunction with educational aids; and (20) students representing Class C, who were used as a control group practicing according to the method followed by the teacher at school. The sample percentage of the research community was (51.28%). One of the most important conclusions of the research is that the use of Carroll's model (educational aids) was the best in acquiring students' basic skills and advancing their actual performance level. The use of Carroll's teaching model plays a fundamental role in the learning process, achieving goals, and investing time and effort compared to the method followed. The research recommendations include benefiting from Carroll's model and educational aids that take into account individual differences in light of effectiveness, skill, and the requirements and objectives of the educational unit to achieve better learning.